Sport Management Internship Quality and the Development of Political Skill: A Conceptual Model - Simon A. Brandon-Lai; Cole G. Armstrong; Kyle S. Bunds (Journal of Applied Sports Management, 2016)
Internships are a key component of sport organizations and the sport management curriculum. Due to the vastness of internships both in academia and the sport profession, it is imperative to understand the effectiveness of internships for both the organization and the intern. While previous research has focused on quality control, the agency’s perspective of internships, the student’s perspective, and how to link the theory to practice, scholars have yet to examine the effects of sport management internships on the development of essential professional skills and/or attributes. Given the political nature of obtaining and keeping a job in the sport business, the purpose of this paper is to propose a conceptual model that allows the effectiveness of a sport management internship to be evaluated according to its effect on the political skill of interns. Understanding the internship as one component of the sport management curricula, the conceptual model links sport management students’ developmental experiences, and internship quality to the development of political skill, and three secondary outcomes (i.e., domain-specific self-efficacy, sport industry identification, and future employment intentions). In doing so a comprehensive method for evaluating the effectiveness of internships that prioritizes the student’s growth is offered.
Keywords: sport management internships; political skill; developmental experiences; self-efficacy